HUMANIZAÇÃO E EDUCAÇÃO NO CÁRCERE: ANÁLISE DA IMPLEMENTAÇÃO DA METODOLOGIA APLICADA PELAS ASSOCIAÇÕES DE PROTEÇÃO E ASSISTÊNCIA AOS CONDENADOS (APAC’S) PARA A FORMAÇÃO E SOCIALIZAÇÃO DOS RECUPERANDOS DO SISTEMA PRISIONAL BRASILEIRO - Ribeiro, João Felipe Silveira (2023)
Humanizing the prison system with ethics is a theme that concerns and verifies how the application of the penalty of deprivation of freedom is facing the disrespect of human rights, facing the brutally inhuman conditions of imprisonment, prison overcrowding and among other common abuses, presenting the devaluation that the system is, performing a vision of the current national prison system and what can be changed. Respecting the fundamental rights of the convicted, starting from this negative scenario of prisons and in counterposition demonstrating the emergence of a method of prison self-management, educational, called APAC Method (Association for Protection and Assistance to Convicts). In this work method, called APAC, there are objectives capable of reformulating with the intention of establishing a very different treatment from what is seen in the existing traditional penal institutes, thus guaranteeing through meticulous work the dignity, respect, human valuation, and integrity of the inmates who need to serve their sentence and the right to a new beginning. Therefore, APAC is based on religious values, its implementation and results, realizing what degree of effectiveness it has achieved and can achieve through the study of the APAC philosophy, its purpose and justification. Thus, placing all necessary confidence in those who participate in the method. It can be seen that the APAC Method is an accessible possibility, working on fundamental criteria for the re-socialization of detainees deprived of freedom.